2010
DOI: 10.1177/0969733010368748
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ perceptions of individual and organizational political reasons for horizontal peer bullying

Abstract: Nurses are exposed to bullying for various reasons. It has been argued that the reason for bullying can be political, meaning that the behavior occurs to serve the self-interests of the perpetrators. This study aims to identify how nurses perceive the relevance of individual and political reasons for bullying behaviors. In February 2009 a survey was conducted with nurses working in a research and training hospital located in Turkey. The results showed that the aim of influencing promotion, task assignments, pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 48 publications
1
48
0
3
Order By: Relevance
“…Employees who had high political tendency boasted lower job satisfaction (3133) whereas there is evidence that job satisfaction may lead to higher levels of political behavior (34). According to one study, in Turkish organizations bullying is a political behavior that some employees show in order to promote their own interests (35). …”
Section: Discussionmentioning
confidence: 99%
“…Employees who had high political tendency boasted lower job satisfaction (3133) whereas there is evidence that job satisfaction may lead to higher levels of political behavior (34). According to one study, in Turkish organizations bullying is a political behavior that some employees show in order to promote their own interests (35). …”
Section: Discussionmentioning
confidence: 99%
“…Aspects of reputation in the context of mobbing are abundantly analysed by different authors in different countries (D'Cruz & Rayner, 2013;Fox & Stallworth, 2010;Harvey et al, 2007;Hugh-Jones & Zultan, 2013;Katrinli, Atabay, Gunay, & Cangarli, 2010;Lutgen-Sandvik, 2008;Lutgen-Sandvik & Tracy, 2012;O'Donnell, MacIntosh, & Wuest, 2010). The damage of mobbing to health is discussed in scientific articles by the following authors: Duffy and Sperry (2007), Yildirim, Yildirim, and Timucin (2007), Testa (2013), Burgi (2014), Garot (2014), andSchindeler (2014).…”
Section: Theoretical Substantiationmentioning
confidence: 99%
“…Stress, poor mental health, and feelings of overwork and inadequacy are all factors influencing individuals to behave in a bullying manner. [65] Cangelosi et al [37] found increased faculty bullying of students occurs due to faculty characteristics such as lack of experience teaching, unfamiliarity with the clinical site, and poor workplace boundaries. In nursing, the goals of reflective practice are to develop critical thinking, critique one's performance or knowledge, highlight learning needs, and develop strategies to meet those needs.…”
Section: Faculty Self-reflectionmentioning
confidence: 99%